Meaning of Knowledgeable Person (Analysis of Al-Quran Surah Az-Zumar verse: 9) - Isri Lailatussa’idah (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2023)
Writing this paper aims to learn to understand and know the meaning of the verses of the Qur'an and to provide knowledge to all of us, especially Muslims, so that we educate children with sincerity and responsibility. This study concludes that what is meant by people who know are people who know the rewards will be received, because of their good deeds and the punishment they will receive if they commit immorality. Meanwhile, those who do not know are those who do not know at all because they do not have the slightest hope of getting a reward for their good deeds and do not expect to be punished and their bad deeds at all.